2015
DOI: 10.1021/acs.energyfuels.5b01491
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene Aggregation Behavior in Bromobenzene Determined By Small-angle X-ray Scattering

Abstract: Small-angle X-ray scattering (SAXS) analyses of an asphaltene (a heptane-insoluble fraction in Canadian oil sand bitumen (CaAs)), at various concentrations in bromobenzene (BB) were performed at a synchrotron facility. BB is the first trial medium in which the aggregation behavior of asphaltenes has been elucidated, and is considered to be one of the "best" pure solvents for CaAs when determining the Hansen Solubility Parameters (HSP). Although the aggregation behavior of the CaAs in toluene (TL) and toluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…McLean and Kilpatrick’s studies showed that asphaltene molecules could be bonded at the interface in the form of aggregates or gel-like structures . The observations accorded with the results of Morimoto et al who analyzed the structural properties of the layer by a small-angle X-ray method . However, discrepancies were proposed by Pauchard et al By fitting the dynamic interfacial tension (DIFT) into the adsorption model of asphaltenes, they considered that asphaltene molecules should adsorb irreversibly at the interface in the form of monomers .…”
Section: Introductionsupporting
confidence: 58%
“…McLean and Kilpatrick’s studies showed that asphaltene molecules could be bonded at the interface in the form of aggregates or gel-like structures . The observations accorded with the results of Morimoto et al who analyzed the structural properties of the layer by a small-angle X-ray method . However, discrepancies were proposed by Pauchard et al By fitting the dynamic interfacial tension (DIFT) into the adsorption model of asphaltenes, they considered that asphaltene molecules should adsorb irreversibly at the interface in the form of monomers .…”
Section: Introductionsupporting
confidence: 58%
“…SAXS data of CaAs at concentrations of 10,000 mg/L (~1 %) in BH-95/05, 83/17, 70/30, 60/40, and 50/50 were obtained at beamline BL6A 7) of the Photon Factory (PF) at the High Energy Acceleration Research Organization (KEK). The asphaltene concentration was lower than the maximum solubility determined and sufficiently low to prevent the effects of interparticle interference 3) . Prior to each measurement, the samples were shaken by hand, ultrasonicated for 10 min, and then allowed to stand for 1 week.…”
Section: Saxs Experimentsmentioning
confidence: 85%
“…Fig. 2 includes the resulting fits for BH-95/5, 83/17, 70/30, 60/40, and 50/50, and the calculated R g values of aggregates were 1.4, 2.2, 2.9, 3.0, and 4.5 nm, respectively, smaller than those in toluene (~5 nm) at the same concentrations using the same asphaltene source 3) . It is interesting that aggregate size in a mixture of poor solvents can be much smaller than that in a good solvent.…”
Section: Asphaltene Dispersion Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Small-angle X-ray scattering (SAXS) was carried out for the particle size measurement of asphaltene aggregates, by a small angle scattering station (1W2A) in the Institute of High Energy Physics, Beijing. Data were processed using the software FIT2D and calculated according to the method reported in literature [12]. crystal were clearly identified.…”
Section: Characterizationmentioning
confidence: 99%